Identification of Olfactory Receptors Responding to Androstenone and the Key Structure Determinant in Domestic Pig - Peidong Yang; Tingting Luo; Shuqi Yang; Anjing Zhang; Yuan Tang; Li Chen; Jinyong Wang; Yongju Zhao; Zhining Zhong; Xuemin Li; Ziyin Han; Yupei Zhang; et al. (Current Issues in Molecular Biology)
Olfactory receptors (ORs) are members of the transmembrane G protein-coupled receptor superfamily, playing a crucial role in odor recognition, which further mediates crucial biological processes in mammals. In sows, androstenone can trigger sexual behaviors through olfaction, but the underlying mechanism remains to be explored. To efficiently and accurately screen pig olfactory receptors responding to androstenone and the key structure determinant, we adapted the high-throughput RNA-seq strategy to screen the altered genes upon androstenone treatment in the olfactory epithelium of pigs, yielding 1397 downregulated genes. Of which, 15 OR genes and 49 OR-like genes were candidate androstenone-responsive genes, and 5 ORs (OR2D2, OR8D1, OR8D2, OR10Z1 and OR7D4) were proven as responsible for androstenone-mediated olfaction in vitro. Among the five ORs, pig OR7D4 has the highest level of androstenone response. To further find the structural determinant, we performed ligand-binding cavity analysis on pig OR7D4 with androstenone, predicted seven potential structural sites and further confirmed that F178 and T203 are the key sites for recognizing androstenone. Nevertheless, the natural non-synonymous mutation M133V (rs696400829) of pig OR7D4 was proven to significantly impair the respondence to androstenone. This is the first time the ORs responding to androstenone in pigs and the key structural determinant of pig OR7D4 were identified, which highlights the significance of investigating the role of OR7D4 in pig reproduction performance in the future.